Security-First Frameworks for Multi-Tenant PaaS Platforms: Challenges and Solutions (Cybersecurity and Network Defense Research, 2021)
The proliferation of cloud computing platforms has led to a significant adoption of Platform-as-a-Service (PaaS) offerings in multi-tenant environments, where multiple customers (tenants) share the same infrastructure while maintaining logical isolation. However, this multi-tenancy paradigm poses unique security challenges, primarily due to the shared nature of the underlying infrastructure, which requires effective mechanisms for ensuring tenant-specific confidentiality, integrity, and access control. This paper proposes a security-first framework designed to address key security concerns in multi-tenant PaaS platforms, specifically focusing on Tenant-Aware Role-Based Access Control (RBAC), encryption challenges, and Identity and Access Management (IAM) systems for robust tenant-specific authentication and authorization.A fundamental aspect of multi-tenant PaaS environments is the proper enforcement of access control mechanisms that prevent unauthorized access to resources and data belonging to other tenants. This paper introduces a Tenant-Aware RBAC model that allows administrators to define roles and permissions in a tenant-specific context, ensuring that users within each tenant have appropriate access to their resources while preventing cross-tenant data leakage. The proposed RBAC model takes into account dynamic environments where tenants can have differing security requirements and access patterns. The paper discusses the inherent challenges in defining, managing, and enforcing RBAC policies in such contexts, particularly considering tenant-specific policies that must be both scalable and flexible to accommodate growing and varying tenant needs.In addition to access control, encryption is another critical aspect of security in multi-tenant PaaS platforms. The shared infrastructure often necessitates the use of encryption to safeguard tenant data both at rest and in transit. This paper explores the challenges associated with implementing encryption in such environments, specifically focusing on the management of encryption keys and the isolation of data between tenants. One of the primary concerns is the management of encryption keys in a way that allows tenants to retain control over their data while also ensuring that platform administrators can manage the security of the underlying infrastructure. The paper proposes an approach for tenant-specific encryption key management that balances control and usability, offering practical solutions to prevent unauthorized access or data leaks between tenants.Another significant challenge in multi-tenant PaaS platforms is the implementation of an effective IAM system for managing tenant-specific authentication and authorization. Given that each tenant may have unique authentication requirements, ranging from traditional username-password schemes to more advanced multi-factor authentication (MFA) mechanisms, a comprehensive IAM system is necessary to support a variety of authentication methods. This paper examines existing IAM frameworks and identifies gaps in their applicability to multi-tenant environments. The paper proposes a modular IAM architecture capable of supporting flexible tenant-specific authentication protocols, ensuring that tenants can customize their authentication mechanisms based on their security requirements without compromising the security posture of the entire platform. Moreover, the paper outlines the use of federated identity management, which allows seamless integration with external identity providers, ensuring that tenants can maintain consistency in their identity management systems while taking advantage of platform capabilities.In this research, the proposed framework is evaluated with respect to its scalability, performance, and flexibility. The paper includes several use cases and case studies to demonstrate the practicality of the framework in addressing the security concerns of multi-tenant PaaS platforms. Specifically, these use cases highlight how the proposed solutions can be applied to real-world platforms, including challenges such as handling varying levels of tenant resource consumption, ensuring proper isolation in shared database systems, and meeting compliance requirements in regulated industries. Additionally, the paper discusses the trade-offs between security and performance, particularly in relation to encryption and IAM systems, providing insights into how to optimize the proposed framework for different deployment scenarios.